Irreality from Linguacognitive Viewpoint: Comparative Aspect of Study (on English and Russian Material) (Proceedings of Southern Federal University. Philology, 2017)
Tatyana N. Nikulshina (Automobile and road institute of Donetsk National Technical University. Gorlovka, Donetsk region)The article is devoted to the investigation of linguistic and cognitive aspects of irreality in English and Russian languages. Since the study of irreality in linguistic and cognitive aspects has no long history the importance is emphasized.The interrelation of the real world and mental activity resulted in irreality is revealed. The notion “irreality” is investigated and detailed. Multi-vector understanding of the notion ‘irreality’ is underlined.The investigation highlights the peculiarities of the notion ‘irreality’ verbalized by nouns in both languages. Wide nomination variety is registered.The analysis of lexical units has resulted in five types of irreality: ‘pure’ irreality, subjective substantialism, scientific substantialism, hypothetical substantialism and illogical substantialism. Suggested classification covers the whole field of irreality. Plurality of types of substantialism indicates the necessity of the research. Nouns denoting ‘pure’ irreality turned out to be the most numerous in both languages. Such conclusion reflects the attitude of the English and Russians to the analyzed notion. The prototype of irreality is not found out because of its ambiguity. Illustrative material (2000 lexical units) is provided to confirm theoretical conclusions made. Quantitative information is highlighted and analyzed.Language is very sensitive to changes in everyday life of people. The appearance of different new lexical units denoting the world of irreality is the result of these changes. New innovations are witnesses of language vitality.Common and different features are reflected. The analysis of nonrelated languages permits to distinguish the cross-linguistic peculiarities and outlines the typological generalizations.This kind of approach is capable of producing further results in studying the world of irreality.Key words: irreality, subjectivity, substantialism, hypothetical, illogical, supernatural, imaginary, fantastic.DOI 10.23683/1995-0640-2017-2-136-143